Qinghaosu (artemisinin): the price of success. - White, N (2008)
Artemisinin and its derivatives have become essential components of antimalarial treatment. These plant-derived peroxides are unique among antimalarial drugs in killing the young intraerythrocytic malaria parasites, thereby preventing their development to more pathological mature stages. This results in rapid clinical and parasitological responses to treatment and life-saving benefit in severe malaria. Artemisinin combination treatments (ACTs) are now first-line drugs for uncomplicated falciparum malaria, but access to ACTs is still limited in most malaria-endemic countries. Improved agricultural practices, selection of high-yielding hybrids, microbial production, and the development of synthetic peroxides will lower prices. A global subsidy would make these drugs more affordable and available. ACTs are central to current malaria elimination initiatives, but there are concerns that tolerance to artemisinins may be emerging in Cambodia.